The Hunt Is On! In Pursuit of the Ideal Stem Cell Population for Cartilage Regeneration - Campbell, T. Mark; Dilworth, F. Jeffrey; Allan, David S.; Trudel, Guy (Frontiers in Bioengineering and Biotechnology, 2022)
Cartilage injury and degeneration are hallmarks of osteoarthritis (OA), the most common joint disease. OA is a major contributor to pain, loss of function and reduced quality of life. Over the last decade, considerable research efforts have focused on cell-based therapies, including several stem cell-derived approaches to reverse the cartilage alterations associated with OA. While several tissue sources for deriving cell-based therapies have been identified, none of the resident stem cell populations have adequately fulfilled the promise of curing OA. Indeed, many cell products do not contain true stem cells. As well, issues with aggressive marketing efforts, combined with a lack of evidence regarding efficacy lead the several national regulatory bodies to put a stop to the use of stem cell therapy for OA until more robust evidence becomes available. A review of the evidence is timely to address the status of cell-based cartilage regeneration. The promise of stem cell therapy is not new and has been used successfully to treat non-arthritic diseases, such as hematopoietic and muscle disorders. These fields of regenerative therapy have the advantage of a considerable foundation of knowledge in the area of stem cell repair mechanisms, the role of the stem cell niche, and niche-supporting cells. This foundation is lacking in the field of cartilage repair. So where should we look for the ideal stem cell to regenerate cartilage? It has recently been discovered that cartilage itself may contain a population of SC-like progenitors. Other potential tissues include stem cell-rich dental pulp, and the adolescent growth plate, the latter of which containing chondrocyte progenitors essential for producing the cartilage scaffold needed for bone growth. In this article, we review progress on stem cell therapies for arthritic disorders, focusing on the various stem cell populations previously used for cartilage regeneration, successful cases of stem cell therapies in muscle and hemopoietic disorders, some of the reasons why these other fields have been successful (i.e. “lessons learned” to be applied to OA stem cell therapy), and finally novel potential sources of stem cells for regenerating damaged cartilage in vivo.